The Performance of Airfoil with Lift Fan During Vertical Take-Off and Landing (VTOL) Condition - Zulkefli, Nur Faraihan; Mohd Ramizu, Mohd Nazreen Izzat; Mohd Nor, Nurhayati (Journal of Computing Technologies and Creative Content, 2016)
This study investigated the performance of electric drive ducted lift-fan propeller in the airfoil during vertical take-off and landing (VTOL) condition. The experiment was conducted using subsonic wind tunnel in two configurations; with and without electric deducted fan (EDF), with three different speeds of lift-fan (50W, 100W and 175W). Three different types of Reynolds number (1.4x105, 2.8 x105, and 4.1 x105) were used to study the aerodynamics forces. The results indicated that airfoil fitted with 175W EDF with low Reynolds number produced significant lift to drag ratio. Thus, it is suitable for vertical take-off and landing (VTOL) purposes.